Gosho I Shelter: observations into the lithic complexities of the Pfupi Industry in northeastern Zimbabwe - Burrett, R. S. (Southern African Humanities, 2021)
Recent excavations at Gosho I Shelter have shown that previously-held views of the Later Stone Age Pfupi Tradition as a single uniform entity are incorrect. Despite the lack of an independent chronological sequence, the various Gosho I assemblages are compared to other dated sites, making possible the identification of significant diachronic variation in the archaeological record of northern Zimbabwe. There are notable changes in quantities of various toolstone used, in the forms and frequencies of lithic and bone tools, as well as with later associated ceramics. Most importantly, the idea of the Pfupi as a lithic industry dominated by backed pieces is invalidated, while the possibility of ceramics made by the late foragers themselves is introduced. Some of these temporal changes probably reflect internal responses to demographic, ecological and/or social challenges faced by the foraging communities themselves, while others, over the last two millennia, indicate their co-existence and adaptation to emerging farming and state societies. To cite this article: Burrett, R. S. 2003. Gosho I Shelter: observations into the lithic complexities of the Pfupi Industry in northeastern Zimbabwe. Southern African Humanities 15: 1-43.